1968
DOI: 10.4315/0022-2747-31.9.269
|View full text |Cite
|
Sign up to set email alerts
|

Flow Characteristics in Holding Tubes of Commercial Egg Pasteurizers

Abstract: Fluid flow theory, as related to the holding of egg products in continuous pasteurization operation, is discussed. The conditions for laminar, turbulent and transitional types of flow; the specific factors in holding tubes that may cause deviations from the anticipated type of flow; and the effects of the viscosities of egg products are outlined. Retention times for laminar flow and the effects on survival of microorganisms are evaluated. Determination of minimum holding times in 10 commercial h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

1972
1972
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…This knowledge is essential for the product development, quality control, sensory evaluation and design and evaluation of the process equipment (Velez-Ruiz, 2002). Several researchers (Kaufman et al 1968;Cornford et al, 1969;Scalzo et al 1970;Tung et al, 1971;Hamid-Samimi et al 1984;Ibarz and Sintes, 1989;Lee et al, 1999;Punidadas and McKellar, 1999;Telis-Romero et al, 2006;Toyosaki, 2010) studied the rheological characteristics of egg and reported Newtonian as well as time-dependent Non-Newtonian flow behaviour of egg. These works are summarized in (Atilgan and Unluturk, 2008).…”
Section: Introductionmentioning
confidence: 97%
“…This knowledge is essential for the product development, quality control, sensory evaluation and design and evaluation of the process equipment (Velez-Ruiz, 2002). Several researchers (Kaufman et al 1968;Cornford et al, 1969;Scalzo et al 1970;Tung et al, 1971;Hamid-Samimi et al 1984;Ibarz and Sintes, 1989;Lee et al, 1999;Punidadas and McKellar, 1999;Telis-Romero et al, 2006;Toyosaki, 2010) studied the rheological characteristics of egg and reported Newtonian as well as time-dependent Non-Newtonian flow behaviour of egg. These works are summarized in (Atilgan and Unluturk, 2008).…”
Section: Introductionmentioning
confidence: 97%
“…Although several researchers [12,13,14,15,16,17,18,19] investigated the rheological properties of liquid egg products, there are different conclusions reported about the rheological behavior of LEPs. The results of these studies showed Newtonian, as well as time-dependent non-Newtonian flow behavior of egg.…”
Section: Introductionmentioning
confidence: 99%
“…Several investigators (Kaufman et al 1968;Hamid-Samimi et al 1984;Hamid-Samimi and Swartzel 1985;Ibarz and Sintes 1989;Ibarz 1993;Punidadas and McKellar 1999;Telis-Romero et al 2006) used Newtonian model to describe rheological behavior of liquid whole egg below 60C. In the present study, Newtonian model (Eq.…”
Section: Discussionmentioning
confidence: 99%